Bond characteristics of high strength lightweight concrete - Mitchell, David William, 1966- (2001)
Thesis (M.Eng.)--Memorial University of Newfoundland, 2002. Engineering and Applied Science Bibliography: leaves 109-113. Future construction of concrete floating platforms for offshore oil exploration and development off the East Coast of Canada may lead to a substantial increase in the use of high strength lightweight (HSLW) concrete in Canada. While HSLW concrete has been extensively used in other areas of the world such as Norway, its use to date in Canada has been limited. HSLW concrete with its improved durability and lightweight characteristics is a very much sought after material in the construction of concrete floating platforms. However, the efficient use of HSLW concrete in Canada is limited by the following two restrictions in the Canadian concrete design code A23.3 (2): first, in calculating the bar development length the maximum permissible value for the compressive strength of the concrete is limited to 64 MPa, secondly for lightweight concrete the minimum development length must be increased by 30%. The objective of this research was to determine the bond strength characteristics of 25 mm and 35 mm deformed reinforcement bars embedded in 80 MPa HSLW concrete and to assess whether or not the code restrictions are justified. -- The experiment consisted of performing a total of 72 pullout and push-in test to evaluate the bond behavior under both monotonic and cyclic loading. The effect of tension and compression along with various rates of loading were investigated for the monotonic tests as well as changing the rate of loading for the cyclic tests. Each of the specimens was confined with 10 mm stirrups, representing a well-confined member that is typical in an offshore floating platform. The concrete used in the experiment had an average compressive strength of 83.1 MPa. The results were evaluated and compared to the work by other researchers on high strength normal weight (HSNW) concrete as well as to the Australian, American and Canadian design codes. -- The results indicated that HSLW concrete behaves very similar to HSNW concrete and the maximum bond stress for HSLW concrete is greater than that of normal strength lightweight concrete. The bond stress versus displacement curve indicates a sharp nearly linear ascending portion of the curve followed by a steep descending portion indicating very brittle behavior, which is characteristic to high strength concrete. The cyclic tests indicated that cyclic loading does not have a significant effect on the bond strength provided that the maximum cyclic displacement is less than the peak load displacement in the monotonic test. A comparison of the test results to the various code equations indicates that the current codes are too conservative for HSLW concrete. In particular it is proposed that the concrete density modification factor for lightweight concrete in the Canadian design code be reduced from 1.30 to 1.10 for the case of HSLW concrete. Finally, it was determined that an expression based on the cubic root of the concrete compressive strength rather than the square root better describes the bond behavior of HSLW concrete.